Effect of Electrokinetic Soil Improvement on CBR Value of Expansive Clay - Darmiyanti, Lydia; Imanuel, Ivan; Prihartono, Prihartono (President University, 2025)
Improvement of low permeability soils with high plasticity index and high shrinkage expansion cannot be done by soil compaction or consolidation. The structure of expansive clays is influenced by the history of soil formation. Expansive soil structure is composed of two tetrahedra with one octahedron. Van der Waals bonds bind them together. Kolinite, illite, and montmorillonite are minerals in expansive soils. Montmorillonite has the weakest bond of the others so that other elements can easily enter the clay structure and bind to it. The ability of clay soil to absorb water or other minerals that come close is due to its cation exchange capacity (CEC). Clay, with its negative ions, will attract positive ions that approach the soil surface. Water with H+ content will easily enter into the structure of the clay soil, bond with it, and cause the soil to swell.Electrokinetic soil improvement is effective on clay soils. With the nature and characteristics of clay soil, positively charged stabilizing ions are required. Positive ions will enter due to the CEC process and affect the mineral content of the soil, thereby improving the physical and mechanical properties of the clay soil. Therefore, this research needs to be conducted to improve clay soil using the electrokinetic method with a calcium dioxide solution. An increase in the Bearing Capacity Ratio (CBR) value occurred after being improved by electrokinetics using four variations of voltage application.The variation of applied voltage gives different results to the change of soil mechanical properties. The original soil CBR of 0.093% increased for all stress applications. The optimum CBR value occurred in the soil applied with 15V. The resulting CBR increase reached 200% of the original soil CBR.